Bimtek Modul Ajar Bagi Guru MTS dan MA Tuban Selatan - Damayanti, Rini; ardiansyah, roely; Hadi, Sueb; kaswadi, kaswadi; Pranoto, Agung; Safitri, Adellia Novisa (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2024)
The Merdeka Curriculum will be implemented simultaneously at the secondary education level in 2024. Even at the junior high school level, especially grade VII, in the 2023/2024 school year, the Merdeka Curriculum has been implemented. The implementation of the Merdeka Curriculum requires teachers' understanding and readiness of the Merdeka Curriculum with its various components and applications. Realistic conditions in the field show that junior high school teachers do not fully understand the Merdeka Curriculum, especially regarding Learning Outcomes, Learning Objectives, Learning Objective Flow, and Teaching Modules and their modifications. The purpose of the service activity is to increase teachers' knowledge, understanding of the Merdeka Curriculum and produce learning tools. The method used in this service is training assistance in the form of workshops. The results of the activity show that the teachers have understood the concept of the Merdeka Curriculum, especially Learning Outcomes, Learning Objectives, Learning Objective Flow, and Teaching Modules and their applications. This can be seen from the work of the teachers in embodying these concepts in the flow of learning objectives and teaching modules as lesson plans to be implemented. In other words, junior high school teachers in the South Tuban Indonesian Language MGMP are not ready to implement the Merdeka Curriculum.ABSTRAKBeberapa kendala yang dihadapi oleh Mitra yang harus dicarikan solusi agar penerapan Kurikulum Merdeka dapat berjalan secara baik, sehingga diharapkan kurikulum ini sebagai pelengkap dan jawaban terhadap kekurangan dari kurikulum sebelumnya yaitu (1) Perubahan mindset guru agar siap dalam menghadapi dan menerapkan Kurikulum Merdeka, (2) Digitalisasi sekolah yang masih rendah, dan (3) Pembelajaran belum berpusat pada siswa. Solusi yang ditawarkan kepada mitra yaitu melaksanakan pelatihan tentang Kurikulum Merdeka agar pengetahuan guru meningkat dan tidak terjadi kebingungan dalam penerapan Kurikulum Merdeka. Luaran yang diharapkan dalam pelaksanaan pelatihan ini meliputi (1) Perubahan Mindset Guru untuk mampu berpikir dengan paradigma baru, (2) Penerapan kurikulum Merdeka dapat berjalan secara optimal, (3) Dihasilkannya Modul Ajar, yang mampu menjawab kebutuhan siswa, (4) Artikel yang diterbitkan pada jurnal Nasional. Metode pelaksanaan Pengabdian Kemitraan Masyarakat meliputi (1) perencanaan dan perancangan, (2) pelatihan, (3) Monitoring dan Evaluasi, (4) Publikasi dan Pelaporan, dan (5) Tindak Lanjut Pasca Program. Kurikulum merdeka merupakan kurikulum baru yang ada di Indonesia. Kurikulum merdeka ini dianjurkan untuk diterapkan di sekolah-sekolah yang di Indonesia dengan beberapa kategori yaitu Mandiri belajar, Mandiri Berubah, dan Mandiri berbagi. Melalui pelatihan yang dilakukan pemahaman guru terkait kurikulum merdeka meningkat.